Telechelic Poly(disulfide)s and Related Block Copolymer. Issue 15 (20th May 2014) - Basak, Dipankar; Kumar, Rajan; Ghosh, Suhrit
<x xml:space="preserve">Abstract</x> In this communication, a mild, efficient, and generalized polycondensation route is developed for poly(disulfide)s from commercially available monomers 2, 2′‐dithiodipyridine and 1, 6‐hexanedithiol. Using the stoichiometric imbalance between the two monomers, it is possible to produce telechelic poly(disulfide)s of predictable molecular weight with reactive pyridyl disulfide groups at both the terminals of the chain. The two terminal pyridyl disulfide groups can be quantitatively replaced by a functional thiol using selective thiol‐disulfide exchange and thus produces functional telechelic poly(disulfide)s, which can be used as a macroinitiator to initiate ring‐opening polymerization of a cyclic lactide monomer generating an ABA‐type triblock copolymer with degradable B block. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>